Effects of different grazing intensities on plant species diversity at different spatial scales in a desert steppe in Inner Mongolia - Changlin Xue; Shijie Lv; Yanling Wu; Jie Yun; Rui Dong; Wentao Wang (PeerJ)
The effect of grazing intensity on plant diversity has been widely studied. In this study, desert steppes with different grazing intensities (no grazing (CK), light grazing (LG), moderate grazing (MG), heavy grazing (HG), and extremely heavy grazing (EG)) in Inner Mongolia were selected to study the changes in species diversity at different spatial scales (α, β, and γ diversity) and the α diversity of different plant groups (dominant species, common species, and rare species).The results showed that the α, β, and γ diversity first decreased and then increased with increasing grazing intensity, and β diversity was observed to be the most sensitive index to the grazing intensity. Grazing had the greatest impact on the α diversity of rare species and the least impact on the α diversity of common species. Therefore, rare species are of great significance for the maintenance and assessment of biodiversity. We concluded that grazing leads to a sensitive response of β diversity, and this sensitive phenomenon is mainly affected by rare species. The results could provide scientific bases for the protection of plant diversity and sustainable grazing in desert steppes.